REFORMULASI KURIKULUM MAJLIS TAKLIM DI ERA TRANSFORMASI DIGITAL - Bahrudin Salim (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research aims to formulate the curriculum formulation of the majelis taklim in the era of digital transformation. This research model is library research using qualitative research methods where the results are in the form of a curriculum formula for the majelis taklim in the era of digital transformation. The results of the study show that the formulation of the majlis taklim curriculum in the era of digital transformation is as follows: creating a website for the majlis taklim, developing a learning management system (LMS), learning resources and teaching materials from the internet selectively, the use of social media, materials and themes of recitation themes adjusted to issues circulating on social media, increasing materials and themes to counteract the spread of religious understanding that is contrary to the spirit of rahmatan lil alamin and contrary to the religious understanding of the majority of muslims (sawadul a'dhom), the provision of language skills and digital natives and given a certificate of expertise, one or two semesters are given mathematics, logic science, science and technology, skills, entrepreneurship and marketing, encouraged by the one product one majlis taklim program along with the digital marketing network, coaching programs through digital native training for ustadz, ustadzah and presenters, worshippers and administrators, as well as the formulation of other majlis taklim curriculum that is attached at all times such as the need to refer to the book of books by Salafusshalih scholars, convey differences of views and arguments (if any). and encourage the ability of pilgrims to create a harmonious atmosphere in the community, so that majlis taklim can carry out religious functions, educational functions, economic functions, socio-cultural functions and the function of resilience and defense of the nation and state.